Pengaruh Pemberian Ekstrak Etanol Buah Pare (Momordica Charantia L) Terhadap Gambaran Histopatolgi Arteri Koronaria Tikus Putih (Rattus Norvegicus) Jantan Galur Sprague Dawley Yang Diinduksikan Minyak Jelant - Joni, Agnesia Priskila; Windarti, Indri; Oktarlina, Rasmi Zakiah; Susianti, Susianti (Medula, 2025)
Coronary heart disease is one of the main causes of death in the world, with more than 17 million deaths every year due to heart and blood vessel diseases, with around 8.7 million of them caused by coronary heart disease and around 15 out of 1000 residents in Indonesia which is equivalent to around 2,78,064 people suffer from coronary heart disease. The high frequency of use of cooking oil means that cooking oil is often used repeatedly. Repeated use of cooking oil can cause damage to various body organs such as the liver, heart, kidneys and arteries. Exposure to free radicals and free fatty acids obtained from used cooking oil if it enters the body will result in oxidative stress. The atherosclerosis process is characterized by the change of k-LDL to Ox-LDL which triggers endothelial dysfunction and the formation of atherosclerotic plaque on the walls of blood vessels. The high fatty acid content in used cooking oil can easily stick to the walls of blood vessels, so that it will accumulate and form atherosclerotic plaque. One of the alternative antioxidants that comes from herbs is bitter melon (Momordica Charantia L). Bitter melon contains flavonoid compounds. Flavonoids are secondary metabolites which are antioxidants that can inhibit free radical activity and can prevent atherosclerosis. Antioxidant compounds can reduce atherosclerosis by inhibiting LDL metabolism in secondary atherosclerotic lesions to prevent LDL oxidation in these lesions.